Noninvasive Surface Detection of Papillary Thyroid Carcinoma by Fourier Transform Infrared Spectroscopy - Zhang, Weitao; Tian, Peirong; Zhu, Qing; Zhang, Yuanfu; Cui, Long; Xu, Zhi (Chemical research in Chinese universities, 2015)
Previously Fourier transform infrared（FTIR） spectroscopy has been applied to detecting thyroid cancer during operations and to discriminating cervical metastatic ones from non-metastatic lymph nodes. This study explored the possibility of establishing a sensitive, accurate and noninvasive screen or diagnosis by preoperative FTIR spectroscopy. 111 patients undergone a thyroid operation and 50 healthy volunteers were enrolled in the study. The FTIR spectra were obtained by two mid-infrared optical fibers with an attenuated total reflectance（ATR） probe closely contacting the subjects＇ skin on the thyroid nodules. The FTIR spectra obtained from normal thyroid, nodular goiter（NG） and papillary thyroid carcinoma（PTC） patients were compared. A Fisher＇s discriminant analysis was created based on these data. There were 41 PTC patients and 70 NG patients according to their histopathological examinations. A total of 23（of 39） parameters were statistically different among the three groups（P〈0.05）. The Fi300 and F1080 parameters were significantly different between the three groups. In total, 9 out of 39 FTIR parameters were selected as independent factors by the Wilks＇ lambda stepwise discriminant analysis. The discrimination accuracy of papillary thyroid carcinoma in the three groups was 88.8%. Surface detection of PTC by FTIR spectroscopy is feasible. FTIR spectroscopy can be used for rapid and noninvasive PTC screen and auxiliary diagnosis.